26.6k views
5 votes
Verify: (x−88)(x+88)=x²−88².

2 Answers

6 votes

Answer:

LHS:


(x - 88) * (x + 88)


= x {}^(2) + 88x - 88x - (88) {}^(2)


= x {}^(2) -( 88) {}^(2)

= RHS

(x -88)× (x+88) = x ² - 88²

User Sjeiti
by
5.9k points
1 vote

Answer:

⇒ ( x − 88 )( x + 88 )

on solving, we get

⇒ x × ( x + 88 ) - 88 × ( x + 88 )

or

⇒ ( x × x ) + 88x - 88x + ( - 88 × 88 )

or

⇒ x² + 88x - 88x - 88²

or

⇒ x² + 0 - 88²

or

⇒ x² - 88² = RHS

Explanation:

Given equation:

( x − 88 )( x + 88 ) = x² − 88²

now,

considering the LHS

we have

⇒ ( x − 88 )( x + 88 )

on solving, we get

⇒ x × ( x + 88 ) - 88 × ( x + 88 )

or

⇒ ( x × x ) + 88x - 88x + ( - 88 × 88 )

or

⇒ x² + 88x - 88x - 88²

or

⇒ x² + 0 - 88²

or

⇒ x² - 88² = RHS

hence verified

User Dean Xu
by
5.6k points